2017
DOI: 10.1149/2.0171703jes
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Energy Harvesting Strategies on Performance and Microbial Community for Sediment Microbial Fuel Cells

Abstract: Sediment microbial fuel cells (SMFCs) are being developed as potential energy sources where remote sensing and monitoring would be useful. Several energy harvesting techniques for SMFCs have emerged, but effects of these different strategies on startup, performance, and microbial community are not well understood. We investigated these effects by comparing a continuous energy harvesting (CEH) strategy with an intermittent energy harvesting (IEH) strategy. During startup, IEH systems immediately produced higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…This was not novel since it was shown in different previous works in which MFCs were combined with external SCs. [41][42][43][44][45][46][47][48][49][50][51][52][53] The novelty of this work stays into measuring the parameters of interests such as ESR and capacitance of the single component and the combined systems. These measurements allow understanding that a proper parallel connection enables a synergic interaction between MFC and SC with improved current and pulse energy performance with respect to those of the separate units.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This was not novel since it was shown in different previous works in which MFCs were combined with external SCs. [41][42][43][44][45][46][47][48][49][50][51][52][53] The novelty of this work stays into measuring the parameters of interests such as ESR and capacitance of the single component and the combined systems. These measurements allow understanding that a proper parallel connection enables a synergic interaction between MFC and SC with improved current and pulse energy performance with respect to those of the separate units.…”
Section: Discussionmentioning
confidence: 99%
“…A successful example of a combination of MFCs with batteries and supercapacitors comes from the robotic field with Gastrobot and EcoBots family . Other practical applications through a combination of supercapacitors and MFCs have also been reported . The different possible combinations of MFC and power management systems are described in detail in a recent review .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to remember that the power source of the EHS are living organisms; for this reason the energy quantity that can be harvested and the frequency with which it must be done has to be taken into consideration. The EHS used in this work was a capacitor-based system operated in an intermittent energy harvest (IEH) mode because it has been reported that it is possible to harvest twice as much energy compared to the continuous energy harvest (CEH) mode [7,[40][41][42][43] and prevent voltage reversal in the cells.…”
Section: Ehs Performancementioning
confidence: 99%
“…Recently, it was found that toxic metals ions acted as electron acceptors of cathode reduction reaction to enhance power production by being reduced to metallic ionic forms (Li et al, 2017). The high efficiency of SMFC with toxic metals ions reducing cathode was linked with the higher over-potential of oxygen than that of toxic metals ions (Hsu et al, 2017). In the SMFC, toxic metals ions are easily transport to the both sides of cathode and anode, revealing that the impact of toxic metals ions on the SMFC efficiency become more complex due to the abrupt balance among biological effect of toxic metals on the microbes of anode and it’s works as an electron acceptor at the cathode (Chen et al, 2016).…”
Section: Introductionmentioning
confidence: 99%